CeO2-TiO2 photocatalyst: Ionic liquid-mediated synthesis, characterization, and performance for diisopropanolamine visible light degradation - Sivalingam, J.R. (Diponegoro University, 2018)
CeO2-TiO2 photocatalyst with Ce:Ti molar ratio of 1:9 was synthesized via co-precipitation method in the presence of 1-ethyl-3-methyl imidazolium octylsulfate, EMIMOctSO4 (CeO2-TiO2-IL). The ionic liquid acts as a templating agent for particle growth. The CeO2-TiO2 and TiO2 photocatalysts were also synthesized without any ionic liquid for comparison. Calcination was conducted on the as-synthesized materials at 400 °C for 2 h. The photocatalysts were characterized using diffuse reflectance UV-Vis spectroscopy (DR-UV-Vis), field emission scanning electron microscopy (FESEM), X-ray powder diffrac-tion (XRD), and surface area and pore size analyzer (SAP). The presence of CeO2 has changed the opti-cal property of TiO2. It has extended the absorption edge of TiO2 from UV to visible region. The calcu-lated band gap energy decreased from 2.82 eV (TiO2) to 2.30 eV (CeO2-TiO2-IL). The FESEM morphol-ogy showed that samples forms aggregates and the surface smoothens when ionic liquid was added. The average crystallite size of TiO2, CeO2-TiO2, and CeO2-TiO2-IL were 20.8 nm, 5.5 nm, and 4 nm. In terms of performance, photodegradation of 1000 ppm of diisopropanolamine (DIPA) was conducted in the presence of hydrogen peroxide (H2O2) and visible light irradiation which was provided by a 500 W halogen lamp. The best performance was displayed by CeO2-TiO2-IL calcined at 400 °C. It was able to remove 82.0% DIPA and 54.8% COD after 6 h reaction. Copyright © 2018 BCREC Group. All rights reserved.